Long-Term Effect of Tillage, Water and Nutrient Management Practices on Mineral Nitrogen, Available Phosphorus and Sulphur Content under Rice-Wheat Cropping System - R.K. Rattan and A.K. Singh, B.C. Verma, S.P. Datta (Journal of the Indian Society of Soil Science, 2016)
The Indo-Gangetic plains of South Asia depends on rice-wheat based cropping system for their food security. Sustainable management of this system is difficult because of differential requirements in respect of soil and environmental conditions. A judicious and scientific management of this system in relation to tillage, water and nutrient is crucial for sustaining productivity. The present paper aims to study the interactive effects of tillage, water and nutrient management practices on mineral nitrogen (N), available phosphorus (P) and sulphur (S) content in soil under rice-wheat cropping system after completion of 7th cropping cycle. Soil samples were collected from a long-term field experiment which was initiated in 2001 at Indian Agricultural Research Institute (IARI) farm. The experiments consisted of two tillage, three water and seven nutrient management practices, which were allocated to main, sub and sub-sub plots (split-split plot design), respectively. Results indicated that, mineral N and available P content in soil was higher in puddled soil as compared to non-puddled condition. The P content in soil decreased with moisture content whereas, available S increased. Organic source of nutrients could not maintain the level of mineral N in soil even as that recorded in control whereas, plots that received FYM and crop residue along with mineral fertilizers showed significantly higher mineral N content than the plot where nutrients were supplied through chemical fertilizers. Integration of crop residues along with mineral fertilizers had a beneficial effect on the availability of P in soil.